Unionized Oligopoly, Trade Liberalization and Location Choice - Kjell Erik Lommerud; Frode Meland; Lars Sørgard (Center for Economic Studies and ifo Institute (CESifo), 2002)
In a two-country reciprocal dumping model, with one country unionized, we analyze how wage setting and firm location are influenced by trade liberalization. We show that trade liberalization can induce FDI, which is at odds with conventional theoretical wisdom and cannot happen in a corresponding model without unionization. FDI is undertaken partly to win a distributional battle with unionized labor, and the incentives to invest abroad can be too large seen from a welfare point of view.
Keywords: D43; F15; F21; J51; 330; unionized oligopoly; economic integration; foreign direct investment